Evaluation of gas fuel and biofuel usage in turbine - Dalya H. Al-Mamoori; Mohanad H. Aljanabi; Ali Assim Alobaidi; Omar Muhammed Neda; Zaid H. Al-Tameemi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Modern gas turbines are a significant source for power generation and prime mover for marine propulsion. The depleting fossil fuel sources have provided a cue for broader implementation and usage of renewable energy. Biofuel has been touted as a substitute for natural gas to power gas turbines. To confirm the dependability and reliability of this attempt in a complex multi-domain system, for example, the gas turbine, the fuel system of the micro-gas turbine is designed and modelled using MATLAB Simulink. The model; simulates the; transient and steady state of a gas turbine’s nominal functional situations. Evaluations between the field data and; simulation outcomes validate a high degree of correspondence. The fuel system in the micro;-gas turbine simulation model is also optimized with the experimental data.